The Differential Effects of Leukocyte-Containing and Pure Platelet-Rich Plasma on Nucleus Pulposus-Derived Mesenchymal Stem Cells: Implications for the Clinical Treatment of Intervertebral Disc Degeneration - Jun Jia; Shan-zheng Wang; Liang-yu Ma; Jia-bin Yu; Yu-dong Guo; Chen Wang (Stem Cells International)
Background. Platelet-rich plasma (PRP) is a promising strategy for intervertebral disc degeneration. However, the potential harmful effects of leukocytes in PRP on nucleus pulposus-derived mesenchymal stem cells (NPMSCs) have seldom been studied. This study aimed at comparatively evaluating effects of pure platelet-rich plasma (P-PRP) and leukocyte-containing platelet-rich plasma (L-PRP) on rabbit NPMSCs in vitro. Methods. NPMSCs isolated from rabbit NP tissues were treated with L-PRP or P-PRP in vitro, and then cell proliferation and expression of stem cell markers, proinflammatory cytokines (TNF-α, IL-1β), production of ECM (extracellular matrix-related protein), and NF-κB p65 protein were validated by CCK-8 assay, real-time polymerase chain reaction, enzyme-linked immunosorbent assay, immunofluorescence, and western blot respectively. Results. NPMSCs differentiate into nucleus pulposus-like cells after treatment of PRPs (P-PRP and L-PRP), and NPMSCs exhibited maximum proliferation at a 10% PRP dose. L-PRP had observably higher concentration of leukocytes, TNF-α, and IL-1β than P-PRP. Furthermore, compared to P-PRP, L-PRP induced the differentiated NPMSCs to upregulate the expression of TNF-α and IL-1β, enhanced activation of the NF-κB pathway, increased the expression of MMP-1 and MMP-13, and produced less ECM in differentiated NPMSCs. Conclusions. Both P-PRP and L-PRP can induce the proliferation and NP-differentiation of NPMSCs. Compared to L-PRP, P-PRP can avoid the activation of the NF-κB pathway, thus reducing the inflammatory and catabolic responses.